(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines lexical units denoting emotions from a linguo-cultural perspective. The study explores the interrelationship between language and culture through the analysis of emotive vocabulary, highlighting the culturally specific features of emotional expression. Words and phraseological units that convey emotions are analyzed in terms of their semantic, connotative, and pragmatic characteristics, as well as their functional role in discourse. The research also investigates similarities and differences in the conceptualization and expression of emotions across different linguocultural contexts. The findings demonstrate that the emotional meaning of lexical units is closely connected with cultural values, mentality, and social experience.